Protective Effect of Abelmoschus esculentus Against Alloxan-induced Diabetes in Wistar Strain Rats. (1st November 2016) - Mishra, Neetu; Kumar, Dileep; Rizvi, Syed Ibrahim
ABSTRACT: Increased oxidative stress has been shown to play an important role in the etiology and pathogenesis of diabetes and its complications. Abelmoschus esculentus (Okra) has been reported to possess many important biological properties. We undertook in vivo studies on male Wistar rats to examine the antioxidative potential of okra in normal and alloxan-treated diabetic rats. Okra extract was administered to control and diabetic rats for 35 consecutive days. Erythrocyte plasma membrane redox system (PMRS) activity ( p < 0.05), erythrocytes lipid peroxidation (MDA) ( p < 0.01), and advanced oxidation protein products (AOPP) ( p < 0.001), increased by 153%, 31%, and 290%, respectively, in response to alloxan treatment, while intracellular reduced glutathione ( p < 0.001) and total antioxidant potential of plasma in terms of Ferric reducing ability (FRAP) ( p < 0.01) decreased by 75% and 22%, respectively, on alloxan treatment. Okra supplementation provided protection to the rats against alloxan-induced changes. Based on the present results, we hypothesize that okra has strong antioxidative potential and may be used as a dietary supplementation in diabetes for prevention of oxidative stress-mediated complications.